Reingeniería de procesos de la empresa Tiendas Industriales Asociadas Tía s.a. sucursal Santo Domingo de los Tsachilas - Ordóñez Abendaño, Julio César (2016)
As the process reengineering, a tool to improve the processes of a company, which is in operation and currently has serious problems in its development and daily production is therefore proposed in this paper, whose overall objective is to re-engineer business processes associated stores AUNT INDUSTRIAL SA BRANCH SANTO DOMINGO ", aimed at improving the current service processes client or those who are deficient, to improve productivity and profitability. This research work was developed based on methods, techniques and procedures whereby the methodological development to reach completion very important for the identification of strategic and operational processes data. Allowing to know which business processes are: Human Resources Management, Administrative Management, Finance and General Services with a total of 480 min .; charging and billing process 10.3 min .; Inventory operations monthly 950 min .; Process thrown away 120 min. Receipt of goods CDN 155 min. Receipt of goods CDF 95 min. Percheo, 480 min. By identifying the critical points are needed to make some adjustments which will be in charge of the administrative business of the same, therefore there will be no cost. By reducing time processes that have obviously saved time and money, so we'll save $ $ 1014,00. Plan for improvements to critical processes, the leaders of each area was appointed, together with the Coordinator of improvements within the different processes and develops an improvement plan for each process where your goal, strategy and goal to be planted whereas it better in the process of charging and billing have declined 6.9 min .; Inventory operations monthly 180 min .; Process thrown away 40 min. Receipt of goods CDN 70 min. Receipt of goods CDF 40 min. Percheo, 60 min. It is very important to note that the processes of Human Resources Management, Administrative Management, Finance and General Services, not been considered for modifications, since according to surveys, it is evident that no serious problems to which they are to be be greater care. This is also because these processes must strictly abide to what is specified in TIA corporate policies, which are enforced. Finally the appropriate conclusions and recommendations are made.